ANALISIS PELAKSANAAN PELAYANAN PUBLIK PERIZINAN DAN NON PERIZINAN BERBASIS ONLINE MELALUI APLIKASI JAKEVO (STUDI KASUS PADA UNIT PENGELOLA PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KECAMATAN SAWAH BESAR - JAKARTA PUSAT) - Rahman, Dinda Aulia; Sholekha, Annisa Ramadhani (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Background Licensing services are mostly accessed by the public. Currently, the Capital Investment and One-Stop Services Office of DKI Jakarta has an application called JakEVO (Jakarta Evolution). However, the JakEVO application is still not widely known by DKI Jakarta residents. Another obstacle is that errors often occur when using the JakEVO application. The purpose of this study was to Analysis of the Implementation of Online-Based Licensing and Non-Licensing Public Services Through the Jakevo Application at the Investment Management Unit and One-Stop Integrated Service in Sawah Besar Sub-District - Central Jakarta. The research approach uses a qualitative approach with descriptive methods. Determination of informants in this study using purposive sampling technique or purposive sampling. Online-Based Licensing and Non-Licensing Public Services Through the Jakevo Application at the Investment Management Unit and One-Stop Integrated Service in Sawah Besar Sub-District - Central Jakarta can be said to be quite running well and in accordance with what is expected by the government and by the community. There are obstacles in terms of the use of technology, officer communication with the public, and the use of the JakEVO Application by service officers and the public in Online-Based Licensing and Non-Licensing Public Services Through the Jakevo Application at the Investment Management Unit and One-Stop Integrated Service in Sawah Besar Sub-District - Central Jakarta. As for overcoming various obstacles, including service officers providing assistance and counseling to the community, communicating either directly to service officers at the sub-district or village office to ask questions or ask for directions or directions, as well as through communication media such as in the comments column, email, telephone, whatsapp and creating bulletin boards as information media and complaint services, conducting training for officers and conducting regular discussions both with fellow officers and with leaders regarding problems that occur with the use of the JakEVO Application.